Tamarind (Tamarindus indica L.) Components as a Sustainable Replacement for Pork Meat in Frankfurter Sausages - Rafael Sepúlveda F. Trevisan Passos; Camila Cristina A. de Sousa; Mauricio C. A. da Silva; Ana M. Herrero; Claudia Ruiz-Capillas; Carlos Pasqualin Cavalheiro (Foods)
Five types of frankfurters were formulated: a control without tamarind (T0) and four samples using 5% tamarind pulp paste (PT5), seeds (ST5), peel (CT5), and a blend of all of them (PSCT5), replacing the same portion of meat. The inclusion of tamarind components led to a reduction in the moisture and protein content of the reformulated frankfurters. In terms of mineral composition, CT5 showed the highest (p < 0.05) calcium content. Additionally, ST5 and CT5 treatments demonstrated the lowest processing loss values. The pH was lower in the PT5 treatment (p < 0.05). Incorporating tamarind components reduced the lightness (L*) of the frankfurters, resulting in darker sausages. However, ST5 exhibited greater redness (a*), while higher yellowness (b*) values were observed in PT5 and CT5 treatments (p < 0.05). Texture analysis revealed no differences (p > 0.05) in hardness and chewiness between T0 and PT5; however, ST5 exhibited the highest values for these parameters (p < 0.05). No variation in the conformational order of the lipid acyl chains due to the incorporation of tamarind compounds was observed related to physical entrapment of these compounds in the frankfurter matrix. Both T0 and PT5 were well accepted by consumers, and scores higher than 7 were observed for overall acceptability and purchase intention. The study demonstrated that incorporating tamarind components, especially pulp paste (PT), is a viable alternative for replacing lean pork meat in frankfurters, improving the sustainable aspects of frankfurter production.